Planetary health and health education in Brazil : towards better trained future health professionals - Walter Leal Filho and João Henrique Paulino Pires Eustachio and Alberto Paucar-Caceres and Melissa Franchini Cavalcanti-Bandos and Cintia Nunes and Carlos Vílchez-Román and Silvia Quispe-Prieto and Luciana Londero Brandli (International journal of environmental research and public health : IJERPH, 2022)
Brazil is Latin America’s largest country and has a strong economy, but it is also characterised by many inequalities. These are very conspicuous in the health sector, particularly in health education, which is expected to modernise according to the planetary health (PH) perspective. This paper describes the health education scenario in Brazil and undertakes an analysis of the postgraduate health programmes and policies in place, identifying the extent to which these support the cause of PH. To achieve this goal, this paper deploys a bibliometric analysis to gain a better understanding of the research streams related to higher education and PH. In addition, it presents and discusses selected case studies in the field and cross-checks documents from the Brazilian Ministry of Education against five domains of PH in education. The results indicate that despite some progress to date and the fact that some programmes are in place, there is a perceived need for policies and efforts from education organisations towards connecting PH principles in the education of current and future health professionals.
Keywords: bibliometric analysis; Brazil; health education; higher education; planetary health